2009
DOI: 10.1089/ars.2009.2692
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Oxidative Stress, Chemoresistance, and Cell Survival

Abstract: The discovery of some additional properties and functions of reactive oxygen species (ROS), beyond their toxic effects, provides a novel scenario for the molecular basis and cell regulation of several pathophysiologic processes. ROS are generated by redox-sensitive, prosurvival signaling pathways and function as second messengers in the transduction of several extracellular signals. A complex intracellular redox buffering network has developed to adapt and protect cells against the dangerous effects of oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(140 citation statements)
references
References 161 publications
4
135
1
Order By: Relevance
“…Consistently, gene set enrichment analysis (GSEA) revealed that STEAP1 silencing regulates gene sets involved in oxidative stress responses, type II conjugation, and proteolysis (Supplementary Table S3), which are part of the oxidative stress phenotype seen in cancer (32,33).…”
Section: Knockdown Of Steap1 Inhibits Proliferation Invasion Anchormentioning
confidence: 70%
“…Consistently, gene set enrichment analysis (GSEA) revealed that STEAP1 silencing regulates gene sets involved in oxidative stress responses, type II conjugation, and proteolysis (Supplementary Table S3), which are part of the oxidative stress phenotype seen in cancer (32,33).…”
Section: Knockdown Of Steap1 Inhibits Proliferation Invasion Anchormentioning
confidence: 70%
“…41 Increased CuZnSOD expression was shown to induce imexon-resistance in myeloma cells. 42 TrxR1 expression and activity is increased in adriamycin-resistant leukemia cells and cisplatin-resistant ovarian cancer cells, and its inhibition using auranofin induced apoptosis in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly relevant as reactive oxygen species are primarily generated at complex I of the ETC, with CcO not normally directly involved in reactive oxygen species generation. This mechanism could be a part of a previously unrecognized adaptive chemoresistance mechanism linking both oxidative stress and drug resistance in cancer leading to suppressed apoptotic signaling (67).…”
Section: Discussionmentioning
confidence: 99%